Kontribusi Motivasi Kerja Operator Sekolah, Kompetensi Operator Sekolah, dan Kepemimpinan Kepala Sekolah terhadap Kinerja Operator Sekolah Dasar di Eks Kawedanan Delanggu Kabupaten Klaten - Nugroho, Budi; , Prof. Dr. Budi Murtiyasa, M.Kom; , Dr.Suyatmini,SE.,M.Si (2016)
The research attempts to find out the contribution of school operator's job motivation, school operator's competence, and School Principal's leadership towards school operator's performance in Eks Kawedanan Delanggu of Klaten regency. The research methodology was qualitative research which used explanative approach. The research population was 140 elementary school operators. The data were taken from 100 school operators as sample which used quote sampling technique. Data collecting technique were taken from questionnaires. Data analysis in this research used descriptive statistic analysis, classic assumption test, multiple regression analysis, t-test, F-test, coefficient of determination (R^2), effective contribution, and relative contribution. The research findings show that there is a significant contribution in school operator's job motivations toward elementary school operator's performance in Eks Kawedanan Delanggu of Klaten regency with effective contribution about 18,3%, There is significant contribution in school operator's competence toward elementary school operator's performance in Eks Kawedanan Delanggu of Klaten regency with effective contribution about 33,1%, There is significant contribution in School Principal's leadership toward elementary school operator's performance in Eks Kawedanan Delanggu of Klaten regency with effective contribution about 14,2% and there is significant contribution of school operator's job motivation, school operator's competence and a School Principal's leadership towards elementary school operator's performance in Eks Kawedanan Delanggu of Klaten regency with determination coefficient (R^2) about 65,6%.